Chemical constituents of Cycas mindanaensis - Ng, Vincent Antonio S. (Animo Repository, 2015)
Chemical investigation of the dichlroromethane extracts of Cycas mindanaensis, a plant endemic to the Philippines afforded a-tocopherol (1), squalene (2), and long chain 1-alkenes (3) from the leaflets;2, β-sitosterol (4) and β-sitosteryl fatty acid esters(5) from the bark; 2, triacylglycerols (6), and hydrocarbons (7)from the roots; 5, 6, anda mixture of 4 and stigmasterol (8) from the petiole and rachis; and 6, fatty alcohols (9) and a mixture of 4 and 8from the megasporophyll lamina. The structures of 1-9were identified by comparison of their NMR data with literature data.